Bioactive Compounds from Hermetia Illucens Larvae as Natural Ingredients for Cosmetic Application - Ko'bayev Juradek Eshmamatovich; Eshmamatova Shahlo Jo'radek qizi (Scientific Trends, 2024)
Due to the sustainable organic matter bioconversion process used as substrate for its development, the Hermetia illucens (Linnaeus) larvae biomass is considered a source of compounds with high aggregate value and quite a promising market. The materials that can be extracted from H. illucens larvae have opened the door to a diverse new field of ingredients, mainly for the feed and food industry, but also with potential applicability in cosmetics. In this review we succinctly describe the larval development and rearing cycle, the main compounds identified from different types of extractions, their bioactivities and focus on possible applications in cosmetic products.
Keywords: Hermetia illucens larvae, biomass composition, bioactives, cosmetic applications.